High Prevalence of Asymptomatic Intracranial Atherosclerosis in Elder Women With Tubal Ligation: Result From a Community-Based Study in Shandong, China - Ma, Xiaotong; Sang, Shaowei; Zhao, Yuanyuan; Wang, Xiang; Ji, Xiaokang; Shao, Sai; Wang, Guangbin; Xue, Fuzhong; Du, Yifeng; Lv, Ming; Sun, Qinjian (Frontiers in Cardiovascular Medicine, 2022)
Background: In addition to traditional cardiovascular risk factors, gender-specific factors may also contribute to intracranial atherosclerosis. This study aimed to comprehensively investigate the association between asymptomatic intracranial atherosclerosis (aICAS) and menstrual or reproductive history (MRH), including menstruation, pregnancy, childbirths, menopause and contraception. Methods: Participants in this study were selected from the Kongcun town aICAS study. MRH was collected through structured case report forms, in which menarche age, menstrual regularity, dysmenorrhea, number of pregnancies, number of childbirths, age of first pregnancy, breastfeeding, menopause, menopause age, and contraceptive methods were all involved. All characteristics were compared by chi-square and non-parametric tests as applicable. Logistic regression model and sensitivity analysis were used to analyze the association between aICAS and MRH. Results: A total of 1052 female participants were involved in this study, of which 5.7% had moderate to severe aICAS. Tubal ligation was significantly associated with aICAS in univariate analysis (crude OR, 2.85; 95% CI, 1.22-6.62; P=0.015). This association was still significant among female participants over 60 years old after multivariate adjustment (adjusted OR, 4.36; 95% CI, 1.55-12.24; P=0.005). Sensitivity analysis showed a similar result (adjusted OR, 3.76; 95% CI, 1.24-11.41; P=0.020). Menopause lost significant association with aICAS after multivariate adjustment (adjusted OR, 1.68; 95% CI, 0.66-4.24; P=0.275). No other MRH factors were found to be associated with aICAS. Conclusions: Tubal ligation may be associated with a higher prevalence of aICAS in Chinese elderly women. This provides a new perspective to study the epidemiological characteristics of ICAS.